Experimental investigation of various energy-absorbing layer materials and sodium alginate viscosities on the jet formation in laser-induced-forward-transfer (LIFT) bioprinting (Journal of applied physics, 2023)
Laser-induced-forward-transfer (LIFT) bioprinting technology has been viewed as a regenerative medicine technology because of its high printing quality and good cell viability. To stabilize the jet to achieve high-quality printing, an energy-absorbing layer (EAL) can be introduced. In this study, three materials (graphene, gelatin, and gold) were utilized as the EAL. The effect of each EAL on the jet generation process was investigated. Besides, the effect of graphene EAL thickness was addressed for various experimental conditions. The jet generation process using sodium alginate solutions with different concentrations (1 and 2 wt. %) was also discussed to investigate the effect of viscosity. The time sequence images of the formed jets utilizing three EALs showed that both graphene EAL and gelatin EAL can promote the formation of jet flow. For the gold EAL, no jet flow was observed. This study provides experimental verifications that the interaction between laser and EAL materials can result in different jets due to various dominant interaction mechanisms. For example, strong absorption in the infrared range for the graphene EAL, strong scattering loss for the gelatin EAL, and strong absorption in the ultraviolet range but weak absorption in the infrared for the gold EAL. We also observed the holes left on the EAL after the printing was completed. The thermal effect is dominant to create regular and round shape holes for the graphene EAL, but it changes to the mechanical effect for the gold EAL because of the existence of irregular and unorganized holes. In addition, we identified the existence of an input laser energy threshold value for a certain thickness graphene EAL. More laser energy is required to break down thicker graphene EALs, which will result in a higher initial jet velocity. Furthermore, we explored the effect of sodium alginate (SA) solution's viscosity on the generated jet. We found that a high-viscosity SA solution can result in a low initial jet velocity, a short jet, and small droplets on the receiving substrate. The findings from this study help determine the mechanisms of EAL–laser interaction with different EAL materials in the LIFT process. This work aims to facilitate the development of new EAL and bioink to achieve stable jet formation and high printing quality in future LIFT bioprinting.